Continuación y renovación del Parque Isla Aventura, Neiva (2022)
My love for the city where I grew up leads me to investigate and base on the factors and possibilities that Neiva has to grow as the capital city of Huila. In other words, this project is based on the projection of the Isla Aventura Theme Park, a projection that seeks to cover economic, cultural, social factors, but above all the intervention of architecture in a central point of the city, in addition to significantly involve the rural environment that this area has because of the wealth that is presented in it. Taking into account the ecological characteristics of t he current Parque Isla and its strategic connection with the city due to its location, it does not have the improvements that have been proposed by the different mayor's offices to beautify and adapt the park for tourist purposes, exalting its different bi ological characteristics, recreational spaces that can be recreated within it, and architectural approaches and interventions. The intention of this urban proposal is to recover these spaces, appropriating the territory in a passive way, generating activit ies within the island park that go hand in hand with its current use: agriculture, animal husbandry, recreation and rest. The project seeks to connect the city through a playful axis that communicates the most important and representative nodes and places at a cultural level in the city of Neiva, this directly connected to the city's boardwalk which is directly related to the project, the latter with an intervention, seeking the purpose of providing architecturally modern spaces to generate interaction with the island park and a relevant connection with it through urban activities within the island park that generate interest to citizens and tourists.